Is Atrial Natriuretic Peptide (ANP) and Natriuretic Peptide Receptor-A (NPR-A) Expression in Human Placenta and Decidua Normal? - Tan, Hongchuan; Lin, Liang; Huang, Liping; Yu, Yanhong (Medical science monitor, 2019)
BACKGROUND Atrial natriuretic peptide (ANP) is a cardiac hormone that regulates blood pressure and the salt-water balance in the blood. It acts through natriuretic peptide receptors (NPR), and the major biologically active ANP receptor is natriuretic peptide receptor-A (NPR-A). Aberrant forms of ANP and its receptors have been reported in patients with preeclampsia. However, whether aberrant forms of ANP or NPR-A are present in preeclamptic placenta, and what their role is in preeclampsia pathogenesis, has not yet been elucidated clearly. The aim of this study was to assess the expression of ANP and NPR-A in the placenta and decidua and its role in preeclampsia development. MATERIAL AND METHODS The expression of ANP and NPR-A in the first-trimester villous and decidua, full-term placenta, and preeclamptic placenta was determined using immunohistochemistry and Western blot analysis. The HTR8/SVneo cell line was used to investigate the role of NPR-A in proliferation, apoptosis, and invasion using Cell Counting Kit-8 analysis, flow cytometry analysis, and a Transwell invasion assay, respectively. RESULTS ANP and NPR-A were localized in the syncytiotrophoblasts, cytotrophoblasts, and trophoblast columns of human first-trimester villous trophoblast cells of decidua, and in the glandular epithelium and extravillous trophoblast cells of decidua. ANP-positive and NPR-A-positive cells in the decidual stroma were clustered around and infiltrated into the vascular wall of the spiral artery undergoing remodeling. NPR-A expression was significantly reduced in preeclamptic placentas, and NPR-A knockdown significantly impaired the invasion ability of HTR8/SVneo cells, although it had no effect on cell proliferation and apoptosis. CONCLUSIONS ANP and NPR-A are involved in human placental development. Decreased levels of NPR-A may contribute to the development of preeclampsia.